Confidence building measures – necessary component establishing Nuclear Weapon Free Zone in the region - Nemov, Alexander (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.25 Mongolian Journal of International Affairs No.14 2007 pp.64-67